Analyzing Speech Functions in the Lyrics of "Blue" by Yung kai - Sagala, Lia Nirwana; Aprilia, Velysa Ayu; Rangkuti, Linda Astuti; Sihite, Meida Rabia; Fransiska, Widia (EXCELLENCE: Journal of English and English Education, 2025)
This study investigates the speech functions found in the lyrics of “Blue” by Yung Kai. The song was selected for its expressive language in portraying longing, imagined affection, and emotional vulnerability. The aim of this study is to examine how interpersonal meaning is conveyed through the use of speech functions. Using a qualitative descriptive method, this research applies discourse analysis based on Halliday’s theory. The lyrics were segmented into clauses and analyzed to identify the types of mood (declarative, interrogative, imperative) and their corresponding speech functions (statement, question, offer, command). The results show that statements are the most frequently used, serving to express emotions, beliefs, and personal commitment. Questions represent uncertainty and longing, while offers and commands indicate emotional closeness and desire. The study concludes that beyond entertainment, the song functions as a medium for expressing deep emotional experiences. This highlights the role of song lyrics as a form of interpersonal communication and emotional expression in contemporary music.